Respostas

2013-08-10T20:08:17-03:00
A-(x+7).(x+5)
x² +5x + 7x +35
x² + 12x + 35......... Bháskara   a=1   b=12  c= 35
-b± √b² - 4*a*c
      2a
-12± √12² - 4*1*35
      2*1
-12± √144 - 140
          2
-12± √4
     2
-12± 
     2
-12+  = -10  =  -5
     2          2
-12-  = -14  =  - 7
     2          2
(-5,-7)

b-(2a+b).(a-2b)
2a²  - 4ab + ab - 2b²
2a² - 3ab -2b²       reordena
2a²  -2b²  - 3ab     agrupa
2(a² - b²) - 3ab      não é a mesma coisa que 2(a-b)²

c-(y-6).(y+5)
y² +5y -6y -30
y² -y - 30           a=1   b= -1  c= -30
-b± √b² - 4*a*c
      2a
-(-1)± √-1² - 4*1*-1
      2*1
+1± √ 1 + 4
      2
+1± √ 5
      2
+1+ √ 5
      2
+1- √ 5
      2

d-(2x+1).(6x³-5x+3)
2x(6x³-5x+3) + 1(6x³-5x+3)
12x^4 - 10x² + 6x + 6x³-5x+3
12x^4 - 10x² + 6x³ +x +3

e-(acubo-1).(2acubo-2a+1)
(a³ -1)*(2a³ - 2a+1)
a³(2a³ - 2a+1) -1(2a³ - 2a+1)
2a^6 - 2a^4 +a³ - 2a³ + 2a-1
2a^6 - 2a^4 - a³ + 2a - 1
2a^6 - 2a^4 + 2a - a³  - 1
2a(a^5 - a³ + 1) - a³ -1

f-(a+x).(acubo-ax+xcubo)
(a+x).(a³ - ax + x³)
a(a³ - ax + x³) + x(a³ - ax + x³)
a^4 - a²x + ax³ + a³x - ax² + x^4
- a²x + ax³ + a³x - ax² + x^4 +a^4
ax (-a + x² + a² - x) + x^4 +a^4        agrupando